PRAKTIK PENAGIHAN HUTANG FINTECH OLEH DANA PAYLATER TERHADAP PEMILIK KONTAK DARURAT DI INDONESIA: Fintech Debt Collection Practices by Dana Paylater Towards Emergency Contact Owners In Indonesia - Aulia Saphira Aini; Siti Nurbaiti (Faculty of Law, Universitas Trisakti, 2025)
This study examines the legal situation of debt collection by Dana Pay later services versus emergency contacts in the financial technology (Fintech) sector in Indonesia. Pay later fintech services, which provide easy access to credit, often raise problems in debt collection practices, especially when emergency contacts become the target of service providers' collection efforts. This research aims to analyze the legal situation of emergency contact holders and assess the compliance of debt collection practices with current regulations, such as OJK Circular No. 19/SEOJK. 06/2023 concerning the ethics of confinement. The research uses a legal normative approach by analyzing secondary data, including laws, legal theories, and case studies. The results show that debt collection from emergency contacts, who have no legal obligations related to the loan, is against the regulations of the OK. Such practices potentially violate privacy rights and create psychological pressure on emergency contact holders. Therefore, there is a need to strengthen the regulation and supervision of fintech providers to ensure compliance with ethical standards of debt collection in Indonesia.